Walking with lilac and light: an anthology of written poetry and illustration graphics / Syara Rossham and Ameiruel Azwan Ab Aziz - Rossham, Syara; Ab Aziz, Ameiruel Azwan (Akademi Pengajian Bahasa, 2021)
Walking with Lilac and Light is an anthology of written poetry and illustration graphics that marks its debut in the theme of youthful, saintly and sentimental perspective that relates to a teenager’s viewpoint. The purpose of this writing is to showcase a high comprehension of a new concept in literature writing. Additionally, the objective is to encourage readers to acknowledge and support literary works written and illustrated by a local writer. The method includes compiling the literature writings which are authentically written followed by proofreading and editing and lastly, generating the illustration graphics which are drawn digitally. The development of the project requires more technicality and precision in which to convert the product into files to be reviewed, preparing the proposal draft and ultimately, submitting the manuscript. The final outcome is to get the product recognized by a book publishing company who is willing to view the writer’s work as well as the proposal and with the hope that it will lead to publication of the writer’s work.